Policy-based routing for mobile ad hoc networks running HTR protocol - Souza, Gabriela Coutinho Machado de (2013)
The increasing growth of mobile devices in the whole world, and the forecasts for the coming years has been indicated by several reports. Nonetheless, this need for ubiquitous collaboration has brought new possibilities and challenges to the scientific community. Mobile Ad hoc Networks (MANETs) emerges in this scenario allowing devices to interconnect autonomously, without the need of a fixed infrastructure, in order to provide communication and information services. Due to such decentralization and the natural constraints of mobile devices, it remains, to this day, a challenge to provide efficient routing for MANETs. In this dissertation we propose new routing enhancements based on policies for MANETs running the HTR protocol. We consider the role(s) a user associated to a device performs within an organization. Hence our policies can guide the routing based on these roles. With this scheme we improve communication according to different business needs and scenario requirements. To this end, we propose a set of policies that affects the routing behavior and present four case studies to present each policy. Then we analyze two policies in terms of end-to-end delay, and nodes’ lifetime. Through simulation we evaluate these metrics while varying parameters such as the amount of nodes participating in the network, the mobility characteristics, and the number of traffic sources. Our results show that it is possible to achieve these goals without causing great impact on the average end-to-end delay and energy consumption, two important metrics in any MANET evaluation. We explore the results in several scenarios and detail our findings, which can provide a different perspective for future MANET applications.